DEVELOPING ANDROID BASED APPLICATION “SPEAK BUDDY TO IMPROVE SENIOR HIGH SCHOOL STUDENT’S SPEAKING SKILL - Ivandes Noel; Yanti Sri Rezeki; Eka Fajar Rahmani; Urai Salam; Wardah Wardah (Jurnal Cakrawala Ilmiah, 2023)
This research was conducted to developing an android based application ”Speak Buddy” to improve senior high school student’s Speaking Skill. The form of this research was (R&D) Research and Development. This research and development were conducted to produce innovative teaching media as suggested by Branch (2009) consisting of three phases namely analysing, designing, and developing. The Analyse phase was to find the actual conditions of students and the teacher. The Design phase was done to prepare the appropriate material to create the application. Develop phase was done to create an essential part of the Android Based Application called Speak Buddy. The designed product was completed after having an internal validation regarding the needs and it is already valid to be used by the internal validator. As the result, Speak Buddy is useable to improve student’s speaking skill, especially the eleventh-grade students of SMA N 1 KET. Hulu.